The discovery of cathode materials for lithium‐ion batteries from the view of interdisciplinarity. Issue 3 (20th July 2022) - Huang, Yunhui
Abstract: In honor of Professor John B. Goodenough for his 100th birthday, this article tries to find the relationship between the discovery of cathode materials for lithium‐ion batteries and the interdisciplinary research in his career. The original ideas of lithium cobalt oxide, lithium manganese oxide, and LiFePO4 came from his early research in solid state physics and from his strong knowledge of chemical structure and bonding. Some examples are given to demonstrate the importance of interdisciplinary interactions among materials, chemistry, and physics. With the rapid development of rechargeable batteries, such interdisciplinarity is further extended to engineering, information, and even artificial intelligence. Although there are still many challenges like energy density and safety in the batteries, we are confident that a better solution will be soon found. Abstract : Yunhui Huang worked with Prof. Goodenough from 2004 to 2007 and received a great benefit in academic research from Goodenough's interdisciplinary thought and scientific spirit.